Roscovitine use for the delay of meiotic progression in prepubertal sheep oocytes - Crocomo, Leticia Ferrari; Ariu, Federica; Bogliolo, Luisa; Bebbere, Daniela; Ledda, Sergio; Bicudo, Sony Dimas [UNESP] (Empresa Brasil Pesq Agropec, 2020)
The objective of this work was to evaluate the efficiency of roscovitine on reversibly inhibiting oocytes from prepubertal sheep at the germinal vesicle (GV) stage, and to investigate the kinetics of meiosis progression after inhibitor removal. Cumulus-oocyte complexes, recovered from Sarda breed lambs aged 30-40 days, were cultured for 6 hours in a maturation medium (control) containing 75 mu mol L-1 roscovitine (Rosco) at 38.5 degrees C and 5% CO2. Then, the complexes were subjected to in vitro maturation (IVM) for 18 or 23 hours, in an inhibitor-free medium supplemented with gonadotropins. The evaluation of nuclear configuration by Hoescht staining, under a fluorescence-inverted microscope, showed that 88.7% of the lamb oocytes treated with roscovitine remained at the GV stage, as observed for the immature ones (97.3%) stained after collection. The inhibitory action was reversible; however, the proportion of oocytes (83.3%) at the metaphase-II stage, after 23 hours of IVM, was significantly higher than that observed after 18 hours (29.5%), in which meiosis was still in progression with 34.2% oocytes at metaphase-I, 11.6% oocytes at anaphase-I, and 18.5% oocytes at telophase-I. Roscovitine is efficient to arrest the nuclear maturation in oocytes from prepubertal sheep; however, despite the reversibility, meiosis progression is delayed, requiring more time to be completed.
Keywords: Ovis aries; cumulus-oocyte complex; inhibitor; lamb; meiosis; nuclear maturation